The Effect Of Intrinsic And Extrinsic Motivation On Employee Performance With Job Satisfaction As An Intervening Variable In The Regional Development Planning Agency For Research And Development (Bappedalitbang) Of Banten Province - Putri, Riztita Chairani; Wiguna, Wahyu; Suparmoko, Muhammad (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
Employee performance is a strategic determinant of public sector organizational effectiveness, including the Regional Development Planning Agency (Bappeda), which plays a central role in formulating development policies. The complexity of tasks in the Regional Development Planning, Research, and Innovation Agency (Bappedalitbang) of Cilegon City and the Bappeda of Serang City necessitates strong intrinsic and extrinsic motivation to achieve optimal performance. This study aims to analyze the influence of intrinsic and extrinsic motivation on job satisfaction and employee performance, as well as to examine the mediating role of job satisfaction in both relationships. The research focuses on employees of Bappedalitbang Cilegon City and Bappeda Serang City as representatives of regional development planning institutions with distinct tasks and challenges. A quantitative research approach was employed, utilizing Partial Least Squares Structural Equation Modelling (PLS-SEM) for data analysis. The sample was determined using the 10 times rule (Hair et al., 2022), resulting in 110 respondents. The findings indicate that intrinsic and extrinsic motivation have a significant positive effect on both job satisfaction and employee performance. Job satisfaction also significantly and positively affects employee performance and serves as a significant mediator in the relationship between both motivational factors and performance.